Floquet Hamiltonian engineering of an isolated many-body spin system - Geier, Sebastian; Thaicharoen, Nithiwadee; Hainaut, Clément; Franz, Titus; Salzinger, Andre; Tebben, Annika; Grimshandl, David; Zürn, Gerhard; Weidemüller, Matthias (Arxiv, 2021)
Controlling interactions is the key element for quantum engineering of many-body systems. Using time-periodic driving, a naturally given many-body Hamiltonian of a closed quantum system can be transformed into an effective target Hamiltonian exhibiting vastly different dynamics. We demonstrate such Floquet engineering with a system of spins represented by Rydberg states in an ultracold atomic gas. Applying a sequence of spin manipulations, we change the symmetry properties of the effective Heisenberg XYZ Hamiltonian. As a consequence, the relaxation behavior of the total spin is drastically modified. The observed dynamics can be qualitatively captured by a semi-classical simulation. Synthesising a wide range of Hamiltonians opens vast opportunities for implementing quantum simulation of non-equilibrium dynamics in a single experimental setting.
Gesehen am 21.10.2021